[des] información: Desinformación en las redes sociales durante la pandemia del Covid - 19 (2020)
During the pandemic generated by Covid 9, social media have become a generator of large amounts of data that allow us to understand on a large scale what is being said and thought about the current situation. Within the information that is shared on social media, there is a large portion that is fake news. Understanding the risk of disinformation and misinformation in a health situation, it was proposed to develop a project based on data collection and the creation of a design methodology that works with data analysis tools and artificial intelligence. In this way, it seeks to counteract the effect of the massive amount of false news that are circulating on social media about Covid-19, providing inputs for the awareness of Colombians about the effect that dis and mis information have on them, as individuals and as part of a community. This project specifically allows us to visualize the panorama of Covid-19 disinformation on social networks through text processing, without leaving out the human side of the personal experiences of Colombians facing disinformation in the pandemic.--Taken from the Degree Document Format.